Constructing solitary pattern solutions of the nonlinear dispersive Zakharov-Kuznetsov equation - İnç, Mustafa (Pergamon-Elsevier Science Ltd, 2009)
In this paper. the nonlinear dispersive Zakharov-Kuznetsov equation was solved by using the sine-cosine method. As a result, new solitary pattern, solitary wave and singular solitary wave solutions were found. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Backlund Transformation; Compacton Solutions; Wave Solutions; Solitons; N); Families